Menstruation and related disorders in Indian adolescent girls: an observational study - Patil, Varsha N.; Nannaware, Dipika T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Menstrual disorders are a common presentation and leading reasons for the physician office visits by adolescents. With this preview, we have made an attempt to evaluate the current changes in the age of menarche, menstruation patterns, the incidence of common menstrual disorders and their etiologies. Aims and objectives of the current study was to evaluate the menstrual disorders, their etiology and treatment modalities in adolescents in tertiary health care setup. Methods: An observational study was carried out on female patients in adolescent age group attending OPD of obstetrics and gynecology, Grant Government Medical College, Mumbai, India. The selected women were explained about the protocol, purpose of the study and were requested to complete the questionnaires to elicit information relating to demographic features, menarche age, and menstrual characteristics. Results were tabulated and analyzed. Results: A total number of 100 cases were included in this study, among them majority were in 16-19 years age group (64%), 79% of the study population belong to the lower class. It was observed that 55% study subject had dysmenorrhoea, 65% had irregular menses, 52% oligomenorrhoea, 13% polymenorrhoea, 28% had menorrhagia, 2% amenorrhea, 10% with PCOS and 2% with endometriosis, 4% with hypothyroidism, 4% with hyperprolactinemia. Most of the study subject responded well to analgesics and hormonal therapy. Conclusions: Menstrual irregularity needs to be evaluated with utmost sensitivity and treated promptly. Lack of sufficient knowledge, awareness regarding menstruation among adolescent girls and social embarrassment should be tackled with education.